PTU-060 Phenotypic Characterisation of Inflammatory Bowel Disease in South Asians in the United Kingdom-Insights into a Shifting Landscape. (4th June 2013) - Boyd, C; Limdi, J K
Abstract : Introduction: The aetiology of inflammatory bowel disease (IBD) remains elusive. The increasing incidence of IBD in developing countries and immigrant populations appears to outpace what genetic influences alone could instigate. There is a relative dearth of literature on the phenotypic characteristics of South Asian immigrant populations. The aim of our study was to define the clinical phenotype of IBD in South Asians in North-West England. Methods: We conducted a retrospective study of 102 patients of South Asian origin attending IBD clinics at our hospital. Clinical data including demographics, disease characteristics (Montreal classification), treatment and blood results were obtained using electronic case records. Results: Of 106 patients reviewed, 55 were male. The median age was 38 years (range 16–80) and mean disease duration was 9.5 years. Seventy-six patients had ulcerative colitis (UC) and 30 had Crohn's disease (CD). Five patients were current or ex smokers (4.7%). Seventeen patients had extra-intestinal manifestations of IBD (16.0%). Of UC patients 37 had pancolitis, 34 left sided disease and 5 had proctitis. Of patients with CD, 3 had ileal disease, 11 colonic disease and 16 had ileocolonic disease. Five CD patients had stricturing disease, 10 had penetrating disease (6 also stricturing) and 15 had non-penetrating, non-stricturing disease. Perianal disease was noted in 3 at diagnosis and in 5 subsequently. Eighty four patients received steroids, topical steroids (31), 5-ASA (99), topical 5-ASA (31), azathioprine (56), 6- mercaptopurine (4), cyclosporine (2), methotrexate (10), infliximab (21) and adalimumab (10). Fifty eight patients received at least one immunomodulatory therapy with the median time to use being 12 months (range 0–276 months). Thirteen patients (7 CD, 3 UC) required surgery (3 total colectomy, 10 subtotal). Mean time to surgery was 4 years (range 0–13 years). Seventeen patients had disease progression leading to Montreal reclassification (median time 60 months; range 1–216 months). Conclusion: We noted a higher prevalence of UC with predominantly pancolonic disease and a significant proportion of CD with penetrating or stricturing disease. The majority of patients required immunomodulatory therapy. Epidemiologic insights from such populations may provide further clues in defining an aetiological paradigm for IBD and should form an important area of further research. A case control study exploring differences is underway at our institution. Disclosure of Interest: None Declared